Caracterização molecular de Echinococcus spp. em bovinos no Rio Grande do Sul e avaliação in vitro e ex vivo do óleo de Melaleuca alternifolia frente aos protoescóleces de Echinococcus ortleppi - Monteiro, Danieli Urach (2016)
Cystic echinococcosis (CE) is a zoonotic disease caused by Echinococcus genus. The larval stage (hydatid cyst) of the parasite causes serious public health problems, and affects various species of animals, causing economic losses to the meat industry. This study aimed to identify samples of fertile hydatid cysts in cattle and characterize them molecularly, analyzing in vitro and ex vivo Melaleuca alternifolia oil activity (tea tree oil - TTO) and its formulation in nanoemulsion (NE-TTO) and saris an (terpinen 4-ol) front to protoscolices of Echinococcus spp. Two thousand three hundred and ninety-six samples with cysts derived from an abattoir in the central region of the RS were analyzed, where 295 samples were classified as hydatid cysts by the presence of protoscolices. In PCR reactions for the 12S gene, 251 positive samples were identified for the group of genotypes G5/G6/G7 (E. ortleppi/ E. canadensis) and 40 samples for the G1 genotype (E. granulosus sensu stricto). In PCR subsequently, 250 samples were positive for G5 (E. ortleppi) and one sample for G7 (E. canadensis). A sample (n=12) of PCR products using the region of cox I gene, which was sequenced and compared with samples deposited in Genbank. Phylogenetic analysis identified three distinct groups E1, E2 and E3, which were grouped in sequences with greater similarity. The organ most affected by echinococcosis in cattle was the lung. After confirming the fertility of the cyst, protoscolices were removed and evaluated for viability using eosin 0.1%. For in vitro testing, concentrations of 2.5, 5 and 10 mg/mL of TTO, 10mg/mL of NE-TTO and 1, 1.5 and 2 mg/mL of terpinen-4-ol were analyzed front to protoscolices of E. ortleppi previously identified, in times of 5, 10, 15 and 30 minutes. For ex vivo test, TTO 10mg/mL and 20mg/mL was injected directly into hydatid cysts of E. ortleppi (n = 20) at times of 5, 15 and 30 minutes, and for each time one aliquot of protoscolices was removed for feasibility detection and implementation of PCR to confirm the species involved in the parasitism. Results of this in vitro study showed the protoscolicidal effect of M. alternifolia in all tested formulations and concentrations. Terpinen-4-ol (2mg/mL) had a better action when compared with the highest concentration of pure oil (TTO 10mg/mL). Nanoemulsion formulations (10mg/mL) showed a good activity front to the protoscolices. In ex vivo analysis, TTO (20mg/mL) showed 100% protoscolicidal action in hydatid cyst in 15 minutes. This study is pioneer in Brazil in identifying the potent effect of protoscolicidal M. alternifolia front protoscolices of E. ortleppi, being this kind of Echinococcus genus responsible for most fertile hydatid cysts analyzed in cattle in RS.